All Optical Speckle Contrast-Based Vibration Sensor for Photoacoustic Signal Detection - Matan Benyamin; Zeev Zalevsky (Sensors, 2022)
Remote detection of photoacoustic signals is a well desired ability, enabling to perform advanced imaging in scenarios where contact is not possible. Various unique solutions have been suggested, including a camera-based speckle contrast photoacoustic detection. In this manuscript, a significant upgrade to the camera-based speckle contrast approach is presented and experimentally demonstrated. This solution is based on all-optical vibration sensing setup. The technique is based on spectral estimation of speckle pattern contrast and relies on several pre-developed works. First, it relies on the suggested application of speckle contrast to vibration sensing, and then on the realization of intensity pattern spectral manipulation, using a shearing interferometer. The method is evaluated and compared to traditional contrast estimation, and demonstrated in several applications in various vibration frequency band such as photoacoustic signal analysis and phonocardiographic heart sounds. The method is also applicable to measuring contrast changes due to a general speckle changing behavior, rather than surface vibration alone.